Warum wir uns mit N.F.S Grundtvigs idealismus-kritischen Abhandlungen beschäftigen - Nägele, Horst (Grundtvig-studier, 1995)
Warum wir uns mit N.F.S. Grundtvigsidealismus-kritischen Abhandlungen beschäftigen By Horst Nägele Horst Nägele begins his article with the statement that circumstantial evidence suggests that the democratic credibility of the Federal Republic of Germany may be questioned. Nägele argues for this view by comparing social conventions in Scandinavia and Germany.He adduces historical material to support his theory of a cultural difference on this point. The criticism levelled by the poet Jens Baggesen at the High German language for its remoteness from reality, is dealt with first. Then follows a discussion of the similar criticism by Grundtvig of the idealistic German philosophy, which, according to Grundtvig, is linked up with the Imperialist inclinations of Germany. Hence Germany’s propensity to .litism which finds expression in the New High German literary language as well as in philosophy. In Grundtvig’s view, the connection between the litist, and therefore Imperialist, unitary culture of Germany and the idealistic philosophy manifests itself in the detachment from reality that is characteristic of Schelling’s philosophy. When Schelling talks about the I that embodies itself, it becomes the image of nothing perceiving itself, in contrast to an I attached to a body. Grundtvig also finds evidence of this German tendency towards a missing sense of reality in Schiller’s poetical works. On a close examination of Grundtvig’s writings, it will appear that Friedrich Schiller’s (quasi-idealistic) tragedies are as a whole seen to convey the notion of heroes being (lifeless) shadows, easily killed. For Schiller’s higher, moral human nature, determined by liberty, cannot conquer death; in Grundtvig’s view, only the spirit of history can do that. Grundtvig’s view of life contrasts, for instance, with Schiller’s drama Wallenstein, where the protagonist chooses of his own free will to submit to death and evil.After discussing Grundtvig’s interpretation of Schiller’s dramas, Nägele returns to Schelling’s philosophy as an example of a tendency in German idealism. As Grundtvig understood it, life depends on truth. Grundtvig attaches importance to immediate actuality (‘fundamental and ultimate reality’) as it is the prerequisite for the conception that the ideal is the cause of .all temporal reality.. Grundtvig’s attitude contrasts sharply with what he calls the delusive view of the German idealistic philosophers who despise the body and annihilate life in order to idolize an egocentric construct, with the disastrous consequence that life doesn’t count. Thus Schelling mixes good with evil, truth with falsehood, since the absolute ideal, reason perceiving itself, is given the highest priority, i.e. preceding reality. According to Grundtvig, what is ideal, what is possible, always depends on reality, on what is real. In Grundtvig’s view, truth can only be perceived by man in his life on earth in contradistinction to falsehood; therefore it is impossible to identify the divine perception of the eternal truth and the human recognition of truth.This is the main line of thought in Grundtvig’s criticism of Schelling’s philosophy. It is Nägele’s argument that this criticism is highly topical since it is reflected in the debate over morals today, in the endeavours to create dignified social conventions, and in the complex issue of the future character of the European community as either a union or a loose cooperative structure.